John Duns Scotus's Reportatio Parisiensis and the Origin of the Supertranscendentals - Smith, Garrett R. (Recherches de théologie et philosophie médiévales, 2018)
John Duns Scotus did not consider in a systematic fashion whether being is univocally common to real being and being of reason, despite the importance of the univocity of being in his metaphysics. The issue does arise in Reportatio Parisiensis I d. 29, an ambiguous text. Though Scotus seems to deny that being is univocally common to real being and being of reason, nevetheless he also allows that the primary division of being is into real being and being of reason. Thus, given that a commonality between these two realms of being is a condition for the emergence of the supertranscendental, some scholars have seen Scotus’s views in Reportatio Parisiensis I d. 29 as anticipating early modern notions of the supertranscendental. The present essay considers the criticism that Peter Auriol directed against Scotus’s position, and the opposite reactions to Auriol by Nicholas Bonetus and Petrus Thomae, who affirm (Bonetus) and deny (Thomae) that being is a supertranscendental.\n4207 \n4207